2023
DOI: 10.1177/14773708231186302
|View full text |Cite
|
Sign up to set email alerts
|

Greenspace in prison improves well-being irrespective of prison/er characteristics, with particularly beneficial effects for younger and unsentenced prisoners, and in overcrowded prisons

Abstract: In this paper, we present evidence of estimated significant associations between greenspace and prisoners’ self-reported well-being, self-harm and violence in prisons in England and Wales. Refining and extending our previous research that estimated the relationship between greenspace and self-harm and violence while controlling for the effects of prison characteristics (e.g. prison size, over-crowding and security level), the findings in the present study show that greenspace remains significantly related to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 41 publications
3
10
0
Order By: Relevance
“…Like Toman and others, we lack health data for incarcerated populations, but instead we are able to deploy proxy data for prisoners' wellbeing in a more general sense, namely data for incidents of self-harm and violence published annually by the UK government. Our contention here is that, as argued by Moran et al [16], high levels of self-harm, violence or both are clearly indicative of a lack of wellbeing, and that as their work has demonstrated, in our study context self-harm and violence are very strongly correlated with poor self-reported wellbeing and a high incidence of mental health problems [16][17][18][19]. We use data from a set of prisons in England and Wales to estimate regression models that relate self-harm and prison violence to indicators of environmental quality, whilst controlling for prisoner and prison characteristics that are commonly found to affect prisoner behavior and wellbeing (e.g., prison size, age of prisoners, age of prisons and percentage of unsentenced prisoners) [21][22][23].…”
Section: Toxic Prisonssupporting
confidence: 56%
See 4 more Smart Citations
“…Like Toman and others, we lack health data for incarcerated populations, but instead we are able to deploy proxy data for prisoners' wellbeing in a more general sense, namely data for incidents of self-harm and violence published annually by the UK government. Our contention here is that, as argued by Moran et al [16], high levels of self-harm, violence or both are clearly indicative of a lack of wellbeing, and that as their work has demonstrated, in our study context self-harm and violence are very strongly correlated with poor self-reported wellbeing and a high incidence of mental health problems [16][17][18][19]. We use data from a set of prisons in England and Wales to estimate regression models that relate self-harm and prison violence to indicators of environmental quality, whilst controlling for prisoner and prison characteristics that are commonly found to affect prisoner behavior and wellbeing (e.g., prison size, age of prisoners, age of prisons and percentage of unsentenced prisoners) [21][22][23].…”
Section: Toxic Prisonssupporting
confidence: 56%
“…The question of what influences prisoner wellbeing features in a set of recent studies by Moran et al [16][17][18][19]. In the absence of direct indicators of prisoner wellbeing, these studies take self-harm and prisoner-on-prisoner violence as indicators of (a lack of) prisoner wellbeing.…”
Section: Concepts and Methodsmentioning
confidence: 99%
See 3 more Smart Citations